Digital Technology as a Support for Social Inclusion in Guidance and Counseling Services - Hidayatul Faridah; Ina Yustiana; Feri Hardiyanto (Pusat Publikasi Nusantara, 2026)
The rapid development of digital technology has significantly transformed guidance and counseling services, opening broader access beyond traditional face-to-face interactions and creating new opportunities for social inclusion, especially for marginalized individuals facing geographic, economic, or social barriers. This study aimed to explore how digital technology can expand access to counseling services, reduce social stigma, and enhance service effectiveness through personalization, while identifying key challenges related to data privacy and security. A qualitative case study approach was employed using purposive sampling. Data were collected through in-depth interviews with digital counseling users, service providers, and mental health technology experts, as well as Focus Group Discussions (FGD), and analyzed through thematic analysis. The findings revealed that digital technology improved accessibility by enabling virtual counseling sessions, reduced social stigma by allowing anonymous service access, and enhanced service personalization through data-driven algorithms. However, concerns regarding personal data protection emerged as the primary challenge. These findings imply that with robust security systems and clear regulatory frameworks, digital technology holds significant potential to create more inclusive, effective, and equitable guidance and counseling services for diverse populations.